The determinants of foreign direct investment and the role of foreign direct investment in Malaysia. - Ngadiman, Nelly. (2009)
There is a growing recognition of the importance of foreign direct investment in contributing to developing countries' economic performance and international competitiveness. From the point of view of developing countries, FDI offers several advantages over borrowing to achieve growth. First, equity financing requires payment only when the investment earns a profit, while debt requires payment irrespective of the economic conditions of the host countries. Second, payments to foreign direct investors are under the purview of the host country, while debt servicing requirements, being dependent on interest rates set in world financial markets, are not as easily controlled by developing countries. Third, only a portion of the profits from direct investment are repatriated as most are reinvested in the host country whereas the principal and interest servicing the debt have to be paid. Finally, direct investment allows the matching of the maturity structure of the earnings from an investment and the repayment of capital used to finance it, with little effect on the short-term financing problems of host countries.